Kai kurios semantinės ir morfologinės anglų ir lietuvių kalbų asmeninių įvardžių savybės - Ambrasas, K. (Kalbotyra, 1970)
An attempt has been made to compare semantic and morphological properties of personal pronouns in English and Lithuanian, to determine similiarities and differences between them. The investigation was carried out applying the principles of systematic comparison of languages (as pointed out by R. Lado), referring to the works of Soviet and foreign linguists and relying on examples of translation from English into Lithuanian. The system of personal pronouns in English is rather similar to that in Lithuanian. Nevertheless, certain formal distinctions are worth noting: 1) the English personal pronoun of the third person it has no formal counterpart in Lithuanian; 2) the English they has two counterparts in the Lithuanian jie, jos; 3) the English you has two counterparts in Lithuanian tu (the second person singular) and jūs (the second person plural). These formal distinctions partly presuppose some semantic differences between the two systems. Both in English and Lithuanian personal pronouns are words of relative and extremely general meaning. They are never used in reference to a particular person or thing, and their meaning is always dependent upon the context. Both English and Lithuanian personal pronouns can be characterized as noun pronouns with more or less similar semantic properties. The morphology of personal pronouns was described in two aspects from the point of view of word-building and from the point view of morphological categories – person, gender, case and number. The personal pronouns in both languages are simple words. Person distinctions in English are expressed by lexical means, whereas in Lithuanian – by grammatical means. These distinctions are related to other grammatical and stylistic pecularities. The personal pronouns in both languages differ as regards their functional burdening. The English personal pronouns have no grammatical category of gender. Unlike their English counterparts, the Lithuanian personal pronouns of the third person possess the category of gender. In English the personal pronouns he, she and nouns are the only lexical indicators of gender, whereas in Lithuanian the gender meaning characterizes not only pronouns, but also other parts of speech which in a sentence are in grammatical agreement. Besides, in Lithuanian the category of gender is represented in two-member opposemes both in singular and plura, whereas jn English opposites of this kind do not exist. It in English is the only “personal” pronoun which indicates lifeless things or “non-persons”. It has no counterpart in Lithuanian. In translations it is substituted by the Lithuanian personal pronouns jis, ji (in different case forms), the Lithuanian demonstrative pronouns tas, to (in different case forms), also the pronoun viskas, the affirmative particle taip, sometimes it is described in the narrative way or has no formal substitution. Both English and Lithuanian personal pronouns possess the category of cal se represented in two-member opposemes in English and in six-member opposemes in Lithuanian. The system of declensions in English personal pronouns is quite different from that in other parts of speech. Unlike their English counterparts, Lithuanian personal pronouns are very similar to nouns, adjectives and other parts of speech as regards their declensions. Suppletivity is a usual phenomenon of the personal pronouns of both languages. The personal pronouns in English have only lexical meaning of number, which is closely related to the whole English grammatical system. As to the category of number, in Lithuanian personal pronouns it is expressed both by lexical and grammatical means; the Lithuanian pronouns aš, tu, mes, jūs do not posses the grammatical meaning of gender, whereas jis, ji do posses this meaning. Though in English there are no dual forms, the dual combination mes du etc. in Lithuanian were compared with the English we both, you both and they both as regards their usage and their inner (mutual) combinability.